Development of the Maharah Qira'ah Test Using the Wondershare Quiz Creator (WQC) Application: From Needs Analysis to Evaluation / Pengembangan Tes Maharah Qira'ah Menggunakan Aplikasi Wondershare Quiz Creator (WQC): dari Analisis Kebutuhan hingga Evaluasi - Nur Marselawati Djafar; Ibnu Rawandhy N. Hula (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2025)
This research aims to develop an assessment test for Arabic reading comprehension skills by utilizing the Wondershare Quiz Creator application. The research method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). In the analysis stage, the needs and problems in the evaluation of Arabic reading comprehension skills were identified. The design stage includes the preparation of product specifications, the formulation of learning objectives, and the selection of materials. The development stage includes the creation of an evaluation tool based on the Wondershare Quiz Creator application. The product implementation was carried out through a trial with 30 students. The evaluation stage was conducted to assess the effectiveness of the product through statistical tests using the Wilcoxon Signed Rank Test, as well as pre-test and post-test. The research results show that the Wondershare Quiz Creator application is effectively used as an evaluation and assessment tool for Arabic reading comprehension skills. The significance value of 0.000 indicates a significant difference between the evaluation results before and after the use of the application. Students gave a positive response to the use of the application, which was considered capable of attracting interest, increasing motivation, and facilitating the evaluation process. This research concludes that the development of evaluation and assessment of reading comprehension skills using the Wondershare Quiz Creator application has been proven effective and can be an alternative for Arabic language teachers in conducting assessments of reading comprehension skills.Abstrak: Penelitian ini bertujuan untuk mengembangkan alat tes penilaian keterampilan membaca pemahaman bahasa Arab dengan memanfaatkan aplikasi Wondershare Quiz Creator. Metode penelitian yang digunakan adalah Research and Development (R&D) dengan model ADDIE (Analysis, Design, Development, Implementation, Evaluation). Pada tahap analisis dilakukan identifikasi kebutuhan dan permasalahan dalam evaluasi keterampilan membaca pemahaman bahasa Arab. Tahap desain meliputi penyusunan spesifikasi produk, perumusan tujuan pembelajaran, dan pemilihan materi. Tahap pengembangan meliputi pembuatan alat evaluasi berbasis aplikasi Wondershare Quiz Creator. Implementasi produk dilakukan melalui uji coba kepada 30 orang peserta didik. Tahap evaluasi dilakukan untuk menilai keefektifan produk melalui uji statistik menggunakan Wilcoxon Signed Rank Test, serta pre-test dan post-test. Hasil penelitian menunjukkan bahwa aplikasi Wondershare Quiz Creator efektif digunakan sebagai alat evaluasi dan penilaian keterampilan membaca pemahaman bahasa Arab. Nilai signifikansi sebesar 0,000 menunjukkan adanya perbedaan yang signifikan antara hasil evaluasi sebelum dan sesudah penggunaan aplikasi. Respon siswa terhadap penggunaan aplikasi dinilai positif karena mampu menarik minat, meningkatkan motivasi, dan memudahkan dalam proses evaluasi. Penelitian ini menyimpulkan bahwa pengembangan evaluasi dan asesmen keterampilan membaca pemahaman menggunakan aplikasi Wondershare Quiz Creator terbukti efektif dan dapat menjadi alternatif bagi guru bahasa Arab dalam melakukan asesmen keterampilan membaca pemahaman.